2019
DOI: 10.5603/fm.a2018.0104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the functional asymmetry of the brain on face morphometry in the university students of mathematics and painting department

Abstract: Background: The face is a complicated structure configurations of which are originated and components integrated during the developmental stages. Almost the whole of face is formed by neural crest cells migrating from the edge of the cranial neural folds to the pharyngeal arcus. Brain is an asymmetric organ both functionally and anatomically. While the left hemisphere is dominant in processing the verbal, mathematical and logical information, the right hemisphere is dominant in processing the perceptual, visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 10 publications
4
12
0
Order By: Relevance
“…Although these researchers indicated a trend for the effect of gender × age for the cerebellum, as in other brain areas, they noted that these differences were not statistically significant (Holland et al, 2014). In line with the findings of a previous study evaluating cerebellum volumes in the 6–9, 10–13 and 14–17 age ranges, there were no statistically significant volumetric differences between the sexes in all age groups in current study (Kosar et al, 2012). In addition, our study partially confirmed the findings of a previous study that reported asymmetry for the cerebellar hemispheres (Giedd et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although these researchers indicated a trend for the effect of gender × age for the cerebellum, as in other brain areas, they noted that these differences were not statistically significant (Holland et al, 2014). In line with the findings of a previous study evaluating cerebellum volumes in the 6–9, 10–13 and 14–17 age ranges, there were no statistically significant volumetric differences between the sexes in all age groups in current study (Kosar et al, 2012). In addition, our study partially confirmed the findings of a previous study that reported asymmetry for the cerebellar hemispheres (Giedd et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Neurogenesis of the cerebellum begins at the 13th week of pregnancy and continues until the second year after birth (Tuna et al, 2014). Cerebellar structures mature actively during childhood and adolescence (Kosar et al, 2012; Oliveira et al, 2021). It has been reported that especially the cerebellum reaches the highest volumetric maturity between the ages of 10 and 13 in both genders (Kosar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for n-st values, in previous studies 2,8,15,16,45,46,57 this distance has been reported as ranging from 73.5 to 79.2 mm in males, and 68.84 to 76.1 mm in females. The present study's results were found to be close to the upper limit of the range in the literature (Supplementary Digital Content, Table 5, http://links.lww.com/ SCS/C32).…”
Section: Vertical Measurementsmentioning
confidence: 65%